The phylogeography of Myotis bat-associated rabies viruses across Canada. - Susan Nadin-Davis; Noor Alnabelseya; M Kimberly Knowles (Public Library of Science (PLoS), 2017)
As rabies in carnivores is increasingly controlled throughout much of the Americas, bats are emerging as a significant source of rabies virus infection of humans and domestic animals. Knowledge of the bat species that maintain rabies is a crucial first step in reducing this public health problem. In North America, several bat species are known to be rabies virus reservoirs but the role of bats of the Myotis genus has been unclear due to the scarcity of laboratory confirmed cases and the challenges encountered in species identification of poorly preserved diagnostic submissions by morphological traits alone. This study has employed a collection of rabid bat specimens collected across Canada over a 25 year period to clearly define the role of particular Myotis species as rabies virus reservoirs. The virus was characterised by partial genome sequencing and host genetic barcoding, used to confirm species assignment of specimens, proved crucial to the identification of certain bat species as disease reservoirs. Several variants were associated with Myotis species limited in their Canadian range to the westernmost province of British Columbia while others were harboured by Myotis species that circulate across much of eastern and central Canada. All of these Myotis-associated viral variants, except for one, clustered as a monophyletic MYCAN clade, which has emerged from a lineage more broadly distributed across North America; in contrast one distinct variant, associated with the long-legged bat in Canada, represents a relatively recent host jump from a big brown bat reservoir. Together with evidence from South America, these findings demonstrate that rabies virus has emerged in the Myotis genus independently on multiple occasions and highlights the potential for emergence of new viral-host associations within this genus.